Lengger Seni Tradisional Perekat Nilai-Nilai Sosial Budaya dan Upaya Pembelajarannya pada Masyarakat Wonosobo - Ari Mulyana; Siti Irene Astuti Dwiningrum (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Lengger was originally a means of fertility ritual ceremonies and was danced by men, but now due to the transformation of social and cultural values in Wonosobo, lengger has turned into a means of entertainment and as a performing art. The dancers are performed by women and the performance also has a more mature concept. The aim of this research is to find out the social and cultural values that occur in Wonosobo society so that Lengger art also changes and learning efforts. This research uses a qualitative descriptive approach using the literature study method. The objectives of this research are: Socio-cultural values of the people in Wonosobo. Lengger transformation form in Wonosobo. Application of socio-cultural values to lengger transformation in Wonosobo. The socio-cultural values of the people in Wonosobo include mutual cooperation, respect for opinions, no distinction between race, ethnicity and religion, tepo selira, tolerance, preserving traditional arts and culture, developing and advancing culture, etc. The form of lengger transformation in Wonosobo occurs when the community takes part and plays an active role in the development of the show. The application of socio-cultural values to the transformation of lengger in Wonosobo for learning lengger art in Wonosobo uses the educational concept of Ki Hajar Dewantara, namely the tricenter of education. The three educational centers include: the family realm, the school realm, and the youth movement (community) realm.